Species-specific foraminiferal calcite oxygen and carbon isotope measurements from DSDP Site 516 - Auderset, Alexandra; Smart, Sandi; Ryu, Yeongjun; Marconi, Dario; Ren, Haojia Abby; Heins, Lena; Vonhof, Hubert B; Schiebel, Ralf; Repschläger, Janne; Sigman, Daniel M; Haug, Gerald H; Martínez-García, Alfredo (In: Auderset, A et al. (2025): Species-specific foraminifera-bound nitrogen isotope and foraminiferal calcite oxygen and carbon isotope measurements from DSDP Site 516 in the South Atlantic over a glacial-interglacial cycle [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.979691, 2025)
This dataset contains species-specific foraminiferal calcite oxygen and carbon stable isotope measurements (δ18O and δ13C) from sediment core samples at Deep Sea Drilling Program Site 516.
Keywords: Foraminifera; Foraminifera-bound nitrogen isotopes; Glacial/Interglacial cycles; Oxygen and carbon stable isotopes; Pleistocene; symbiosis